IMPLEMENTASI TEKNIK MINDFULNESS TERHADAP MOTIVASI BELAJAR SISWA KELAS VI SDN PABERASAN I SUMENEP - Risma Rosita, Zanuar Ajeng; Mestika Dewi, Ike Yuli; Hardiansyah, Framz (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This research aims to determine the implementation of mindfulness techniques on the learning motivation of class VI students at SDN Paberasan I Sumenep. Motivation to learn is an important factor in educational success, but initial observations show that students have a low level of concentration and enthusiasm in learning. One approach that can be used to increase learning motivation is mindfulness techniques, which involve mindfulness exercises such as breathing, focusing on the body, and visualizing learning goals. This research uses a mixed method with a Concurrent Embedded design, where the qualitative approach is dominant and quantitative data is used as support. Data was collected through observation, interviews and questionnaires, with total sampling involving all sixth grade students as research subjects. The data analysis technique used is qualitative descriptive analysis for interview and observation data, as well as descriptive statistical analysis for questionnaire results. The research results show that the implementation of mindfulness techniques has a positive impact on students' learning motivation. Observations show that students become more focused, relaxed and enthusiastic in learning. Interviews with students also confirmed that this technique helps them be more enthusiastic and confident in learning. The questionnaire results show an average percentage of 74.58%, which is included in the "good" category according to the Likert scale. Thus, it can be concluded that mindfulness techniques provide good results on student learning motivation. This technique can be applied by educators as a learning strategy to create a more conducive and enjoyable learning environment. This research aims to determine the implementation of mindfulness techniques on the learning motivation of class VI students at SDN Paberasan I Sumenep. Motivation to learn is an important factor in educational success, but initial observations show that students have a low level of concentration and enthusiasm in learning. One approach that can be used to increase learning motivation is mindfulness techniques, which involve mindfulness exercises such as breathing, focusing on the body, and visualizing learning goals. This research uses a mixed method with a Concurrent Embedded design, where the qualitative approach is dominant and quantitative data is used as support. Data was collected through observation, interviews and questionnaires, with total sampling involving all sixth grade students as research subjects. The data analysis technique used is qualitative descriptive analysis for interview and observation data, as well as descriptive statistical analysis for questionnaire results. The research results show that the implementation of mindfulness techniques has a positive impact on students' learning motivation. Observations show that students become more focused, relaxed and enthusiastic in learning. Interviews with students also confirmed that this technique helps them be more enthusiastic and confident in learning. The questionnaire results show an average percentage of 74.58%, which is included in the "good" category according to the Likert scale. Thus, it can be concluded that mindfulness techniques provide good results on student learning motivation. This technique can be applied by educators as a learning strategy to create a more conducive and enjoyable learning environment.